2019
DOI: 10.1016/j.rvsc.2019.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stress on somatic cell count and milk yield and composition in goats

Abstract: There is little information about the effect of the stress on Somatic Cell Count (SCC) and milk yield and composition in goats. A total of 40 goats in their 4 th month of lactation were assigned to two groups: stress (STR) and untreated (CON). Goats of STR were exposed to acute stress (visual and auditory stimulus from a barking dog for 20 minutes on day 0). After the stress, average values of plasma cortisol were higher in STR than CON (P < 0.001); likewise, in STR group cortisol was lower in parity 1+2 goats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
(47 reference statements)
0
12
1
Order By: Relevance
“…Furthermore, the cumulative effect of challenges led to a significant decrease in milk yield during the last challenge (on day 154 of lactation) and on subsequent days of lactation (on days 155, 160, and 161 of lactation) when compared to control goats (Figure 1). Other studies have associated cortisol and SCC increases with an increase in the apoptosis rate in mammary glands and a consequent increase in the number of mammary epithelial cells in the milk of stressed animals (Romero et al, 2015;Mehdid et al, 2019). However, as cortisol is considered an immunosuppressor, the higher SCC observed in the present study cannot be explained by an increase in defense cells in milk (Gonçalves et al, 2017).…”
Section: Table 2 Effect Of Treatment (T) Sampling Hour (H) and Their ...contrasting
confidence: 52%
“…Furthermore, the cumulative effect of challenges led to a significant decrease in milk yield during the last challenge (on day 154 of lactation) and on subsequent days of lactation (on days 155, 160, and 161 of lactation) when compared to control goats (Figure 1). Other studies have associated cortisol and SCC increases with an increase in the apoptosis rate in mammary glands and a consequent increase in the number of mammary epithelial cells in the milk of stressed animals (Romero et al, 2015;Mehdid et al, 2019). However, as cortisol is considered an immunosuppressor, the higher SCC observed in the present study cannot be explained by an increase in defense cells in milk (Gonçalves et al, 2017).…”
Section: Table 2 Effect Of Treatment (T) Sampling Hour (H) and Their ...contrasting
confidence: 52%
“…In contrast, milk yield and composition of VTs does were not affected, remaining similar to the NC group. Increased SCC levels in VTc and FT milk suggest poorer breast health condition and milk quality in these groups [55]. Thus, overall results indicated that a more reduced lactation performance was exhibited by FT and VTc does compared to the NC group, leaving that of the VTs unaltered.…”
Section: Discussionmentioning
confidence: 80%
“…distribution (disregarding SCC) is similar in L and H group (27.3–35.3%, Table 3 ). Higher SCC levels in our study might have been caused by factors other than MCB, e.g., the animal’s physiology, genotype [ 27 ], or by other non-infectious factors such as estrus, seasonal influences, or parity [ 28 , 29 ]. External stresses experienced by the animal can also influence milk SCC [ 2 , 29 ].…”
Section: Resultsmentioning
confidence: 99%